Pleomorphic Adenomas of the Parapharyngeal Space - İstemihan Akın; Tuğba Karagöz; Murad Mutlu; Mehmet Şahan; Evrim Önder (Case Reports in Otolaryngology)
Background. Parapharyngeal space is one of potential facial planes for neoplasms and infections and represents less than 1% of all head and neck tumours. Occurrence of the pleomorphic adenoma in the parapharyngeal space is a rarity. Case Presentation. Here, three giant pleomorphic adenomas of different sizes occupying the parapharyngeal space in three patients are reported. Extensive preoperative diagnostic workup was done in order to verify the nature and size of the tumour and the proximity to the large vessels. Review of the literature, clinical features, pathology, radiological findings, and treatment of these tumours are discussed. Conclusion. The excision of the tumor through submandibular transcervical approach, without cutting the mandible, turned out to be a safe and radical approach in all three cases.